Pengaruh Kualitas Pelayanan Pasien Rawat Inap Dengan Mengunakan Jaminan asuransi Terhadap Kepuasan Pelanggan Di Rumah sakit X Tangerang Tahun 2021: The Influence of the Quality of Inpatient Services Using Insurance Guarantees on Customer Satisfaction at Hospital X Tangerang in 2021 - Haerunisa milawaty; Leo Alexander Tambunan (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2022)
This study aims to determine how service quality can have an influence on customer satisfaction at hospital X Tangerang. The benefit of this research is to be able to build and provide even better services and be able to increase customer confidence to return for treatment at hospital X Tangerang. This study uses a questionnaire as a method of collecting data on respondents' perceptions. And for the analysis technique used quantitative analysis. The results of this study indicate that there is an influence between Service Quality (X) on Customer Satisfaction (Y) with a determination coefficient of 75.5%.